Pengembangan Instrumen Skala Keterampilan Mendengarkan Mahasiswa Calon Konselor - Iklima, Iklima; Latif, Suciani; Fitri, Qawiyyan (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The purpose of this study was to develop a scale instrument for listening skills for prospective counselor students. This study used quantitative descriptive with research and development methods. Participants were selected using purposive sampling with a total of 269 students. Data from this study were analyzed using the RASCH model using the winstep application. The analysis carried out was in the form of validity and reliability tests. The results of the research data showed that there were 16 valid question items and 11 invalid question items, then the research data was reliable with a Cronbach's alpha value of very good.